An ethic of care in the legal profession: Not for women only - Camille A. Carr (Adult Education Research Conference, 1994)
This study examines how lawyers with an ethic of care handle conflicts between their personal values and professional ethics. Lawyers maximize their ethic of care by being selective in their practice, extending responsibility, and by being person centered. Conclusions and implications for continuing and legal education are drawn.